A educação ambiental e a saúde pública na atualidade brasileira. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
Environmental education is necessary and urgently must be developed in all sectors, in order to seek a quality environment; it must also be contextualized to local health, highlighting care with the prevention of diseases and management of environmental factors that may be harmful to human health, in which the physical environment can be discussed, as these may affect the quality of life of the residents of the region., but also socio-environmental problems. In Brazil, Law No. 9,795, of April 27, 1999, provides for the National Environmental Education Policy, and other provisions. The main objective of the research was based on identifying studies that use environmental education in public health or primary care in Brazil, using the production of knowledge, in the light of quantitative/qualitative analysis. Publications related to the field of "environmental education in Brazilian public health" carried out between June and December 2021 were analyzed from two sources available on the internet: Scientific Electronic Library Online (Scielo) and Periodical of the Coordination of Improvement of Higher Education Person (CAPES), found on the Web of Science - WoS. Seventy-six (76) articles were found that related the themes of environmental education and public health in Brazil. The triennium 2015, 2016 and 2017 were the years with the most publications. Among the journals that publish the most on environmental education and public health, it was noted that public health and nursing journals have been standing out.
Keywords: Educação ambiental; Saúde pública; Periódicos científicos; Publicações especializadas; Interdisciplinaridade. Educação ambiental. Saúde pública; POLÍTICAS PÚBLICAS, DIVERSIDADE E DESENVOLVIMENTO AMAZÔNICO; Políticas públicas, diversidade e desenvolvimento Amazônico